Gender Bias and Structural Injustice in the Labor Market: Discrimination Against Single Men amid Increasing Female Labor Participation - M. Ali Muhtarom (Journal Discrimination and Injustice, 2025)
Shifts in gender roles within local labor markets have generated unequal access to employment, giving rise to forms of social injustice manifested in discrimination against single male workers, particularly in rural settings. This article examines how the increasing labor participation of women in Rumbia Subdistrict, Central Lampung Regency, interacts with patriarchal social constructions and informal labor practices, thereby producing patterns of labor exclusion based on gender and marital status. The study aims to: (1) identify the forms of employment discrimination experienced by single men; (2) analyze the structural roots of such injustice; and (3) formulate a problem-solving approach to gender justice. This research employs an implementative qualitative approach through in-depth interviews, field observations, and document analysis. Data sources include female workers, single male job seekers, community leaders, village officials, and local business actors. Data were analyzed using the mubādalah perspective as a supporting theoretical framework, which emphasizes principles of reciprocity, mutuality, and gender equality in social relations. The findings indicate that discrimination against single men constitutes a product of patriarchy-based structural injustice, which simultaneously constrains women’s access to equitable employment opportunities. This dynamic creates a paradox of gender equality within local labor practices. Academically, this study contributes to gender and labor studies by integrating a progressive Islamic perspective (mubādalah) into the analysis of social injustice. From a policy perspective, the article recommends the formulation of non-discriminatory local labor policies, the strengthening of community-based gender education, and the reformulation of village-level labor regulations to foster a fair and inclusive employment system amid ongoing transformations in gender roles.